An Inventory of the Butterfly Species( Lepidoptera: Rhopalocera) of the Upper Imbang-Caliban Watershed, North Negros Rainforest Reserve, Philippines - Slade, Eleanor; Turner, Craig (Silliman Journal, 2022)
Coral Cay Conservation (CCC) recently completed an inventory survey of the butterfly fauna of the Upper Imbang-Caliban watershed area of the North Negros Forest Reserve (NNFR), Negros Occidental, Philippines. The NNFR is one of the last significant areas of moist tropical forest in the Negros-Panay Faunal Region of the Philippines and therefore is considered to be vital for the conservation of a high number of forest-dependent and endemic species. The inventory results revealed that 45% of all species and 84% of sub-species recorded were Philippine endemics, with 21% of sub-species recorded occurring only on Negros. This is the first published account of the butterfly species in the NNFR and highlights the relative importance of the NNFR for the conservation of endemic and restricted-range butterfly species and the need for long-term conservation management of the remaining forest area. Suggestions for conservation and sustainable management of the butterfly fauna of the NNFR are discussed.